2022
DOI: 10.3390/en16010177
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Real-World Non-Exhaust Particulates from Vehicles

Abstract: The need to regulate the non-exhaust particulate matter (PM) emissions from vehicles has been discussed worldwide due to the bad environmental impact and the toxicity to the human body. In-depth studies have been precisely conducted on the analysis of the non-exhaust particulate matters, in particular, the amount of tire, brake and road wear particles and their proportion in the atmosphere. In this study, the influence of tire and road wear particles (TRWP) on PM in the atmosphere was investigated with tire an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Particle sampling systems and their placement on vehicles were also usefully covered. A timely paper by Harrison and Alghamdi 8 (64 references) reviewed the relative merits of various inorganic and organic tracers characteristic of species present in tyre particles as exemplified in a study 9 that used ICP-MS and pyrolysis GC-MS to measure elemental and organic tracers and in another study 10 that used MC-ICP-MS, XAFS and μ-XRF techniques to measure the isotopic and speciated forms of a Zn marker element contained in size-segregated airborne particles. A review paper (263 references) by Zuo et al 11 is recommended for a wider oversight on the use, challenges and future perspectives of stable isotope tracers (Cu, Fe, Hg, Nd, Pb, Si, Sr and Zn) for the source tracing of APM.…”
Section: Air Analysismentioning
confidence: 99%
“…Particle sampling systems and their placement on vehicles were also usefully covered. A timely paper by Harrison and Alghamdi 8 (64 references) reviewed the relative merits of various inorganic and organic tracers characteristic of species present in tyre particles as exemplified in a study 9 that used ICP-MS and pyrolysis GC-MS to measure elemental and organic tracers and in another study 10 that used MC-ICP-MS, XAFS and μ-XRF techniques to measure the isotopic and speciated forms of a Zn marker element contained in size-segregated airborne particles. A review paper (263 references) by Zuo et al 11 is recommended for a wider oversight on the use, challenges and future perspectives of stable isotope tracers (Cu, Fe, Hg, Nd, Pb, Si, Sr and Zn) for the source tracing of APM.…”
Section: Air Analysismentioning
confidence: 99%
“…Isoprene and dipentene are used for the analysis of NR components in TWP as the marker. In general, dipentene is used for building a calibration curve for the quantification of NR components in TWP [ 2 , 3 , 36 , 37 ]. In addition to the sample size, the crosslink density of a rubber vulcanizate influences the production rates of isoprene and dipentene [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies in our lab had shown that 4-vinylcyclohexene was an appropriate marker for the mix of cryo-milled car and truck tyre tread used to establish an external calibration curve. This marker has also been used by several other studies to quantify car tyre material (More et al, 2023;Mun et al, 2022). The tread material was sourced from Denmark and Sweden (Genan, Denmark), i.e., following the suggestion of Miller et al…”
Section: Twp Analysismentioning
confidence: 99%